Paradoxical Influence of the Islamicized School Education in Iran since the 1980s on Performance - Matti, Nathalie (Journal of Persianate studies, 2014)
Abstract After the 1979 revolution, the education system in Iran was reformed. In order to create a “new individual integrated in the Islamic society” (Paivandi, 14), at the beginning of the 1980s, the Iranian regime put the issue of learning at the center of the construction of a new society with a strong Islamic identity. The implications of the reformed school in the aesthetic field, and in particular in actresses’ performances, created very tight meshes, linking together the active and the passive learning of the Iranian population. Nevertheless, it is possible to understand its complexity through the observation and analysis of actresses’ performances in the theater and cinema, considering it as a laboratory of life that gives us access to the realm of the senses.